Mawar Kasih Orphanage Free of Scabies and Fungus, Through Socialization of Healthy Living and Utilization of Sulfur Soap - Wafa, Ali; Rizka; Devi Agustini; Qalbiy Sinta; Putri Robiatul (Yayasan Kajian Riset Dan Pengembangan Radisi, 2024)
Orphanages, or child social welfare institutions, are places where neglected children live together to ensure a decent life. The routine of sharing facilities and the humid conditions of Mawar Kasih Orphanage, make the residents of the orphanage experience skin diseases caused by lice (scabies) and fungi. As a result, the residents experience uncomfortable conditions or interfere with learning, playing, and sleeping/resting activities. Objective: This empowerment activity aims to solve the partner's problem, by breaking the chain of transmission of skin diseases, caused by lice and fungi that continue to recur. This activity will involve 37 residents of the orphanage, to be involved in socialization, implementation/tutorial, and monitoring activities. The problem analysis, plan development, and evaluation activities are carried out by the team and the caregivers of the orphanage. This empowerment activity is carried out for 3 months productively. The residents of the orphanage have participated in the entire series of empowerment activities according to the agenda. Tutorial and monitoring activities carried out by the team, can be well understood and result in positive behavioral changes towards environmental hygiene. The sulfur soap used by the residents of the orphanage, can effectively stop the transmission of lice and mold in the second month.